1997
DOI: 10.1097/00001756-199712010-00034
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine metabolite levels in CSF of SIV-infected rhesus monkeys (Macaca mulatta)

Abstract: Increasing evidence suggests the involvement of the basal ganglia in HIV-1-infected patients. We used SIV-macaques, an animal model of HIV-1 infection, to investigate changes in CSF biogenic amine metabolites over time and compared them with control animals. The dopamine and serotonin metabolites, 3,4-dihydroxyphenylacetic acid (DOPAC), homovanillic acid (HVA) and 5-hydroxyindoleacetic acid (5-HIAA), were analysed by reverse-phase chromatography with electrochemical detection. DOPAC concentrations were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…CSF DA concentration was measured using a reverse-phase high-pressure liquid chromatography system (Agilent 1100, Waldbronn, Germany) and detected by electrochemical detection (Koutsilieri et al 1997). For qualitative and quantitative analyses, we compared retention times and peak heights with those from commercially available standards (Sigma, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…CSF DA concentration was measured using a reverse-phase high-pressure liquid chromatography system (Agilent 1100, Waldbronn, Germany) and detected by electrochemical detection (Koutsilieri et al 1997). For qualitative and quantitative analyses, we compared retention times and peak heights with those from commercially available standards (Sigma, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Peaks were recorded by means of an integrator (HP Chem Station 2/3; Agilent). All settings, columns, and solutions were the same as described elsewhere [17]. Qualitative and quantitative analyses were performed by comparing retention times and peak heights with those obtained with commercially available standards (Sigma, St. Louis, MO).…”
Section: Transcranial Sonographymentioning
confidence: 99%
“…Similarly, CSF homovalinic acid levels are diminished in patients with AIDS and more severely so in patients with AIDS dementia (Larsson et al, 1991;Berger et al, 1994). A study of monoamine metabolites in CSF of asymptomatic SIV infected rhesus macaques showed increased levels of 3,4-dihydroxyphelnyl acetic acid suggesting increased dopamine turn over in early stages of infection (Koutsilieri et al, 1997b).…”
Section: Da Abnormalities In Cerebrospinal Fluid (Csf) Of Patients Wimentioning
confidence: 99%